2009
DOI: 10.1088/0253-6102/51/6/32
|View full text |Cite
|
Sign up to set email alerts
|

Electronic States of a Shallow Hydrogenic Donor Impurity in Different Shaped Semiconductor Quantum Wells

Abstract: The shallow hydrogenic donor impurity states in square, V-shaped, and parabolic quantum wells are studied in the framework of effective-mass envelope-function theory using the plane wave basis. The first four impurity energy levels and binding energy of the ground state are more easily calculated than with the variation method. The calculation results indicate that impurity energy levels decrease with the increase of the well width and decrease quickly when the well width is small. The binding energy of the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The shape of the potential manipulates the energy levels and wave functions which can be applied to specific devices. Study of electronic as well as optical properties of NS-QW systems has been made to explore their use in novel electro-optic devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Parabolic quantum wells have been shown to provide a small leakage current for infrared detector applications [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The shape of the potential manipulates the energy levels and wave functions which can be applied to specific devices. Study of electronic as well as optical properties of NS-QW systems has been made to explore their use in novel electro-optic devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Parabolic quantum wells have been shown to provide a small leakage current for infrared detector applications [1].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the refractive index and optical absorption coefficients due to temperature, external fields and hydrostatic pressure have also been explored for a graded quantum well under intense laser field [11]. Attempts have been made to calculate impurity states for a hydrogenic donor in the square, parabolic and V-shaped QWs and it has been shown that the electron wave function strongly confines in NS potentials than in square one for higher well width [14]. Light emitting diodes are designed with asymmetric triangular multiple QW structures which have improved electroluminescence emission efficiency than the square QW [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation